Direct estimation of the mutation rate at dinucleotide microsatellite loci in Arabidopsis thaliana (Brassicaceae) - Marriage, Tara N. (2009)
The mutation rate at fifty-four perfect (uninterrupted) dinucleotide microsatellite loci is estimated by direct genotyping of 96 Arabidopsis thaliana mutation accumulation lines. The estimated rate differs significantly among motif types with the highest rate for AT repeats (2.03 × 10(−3) per allele per generation), intermediate for CT (3.31 × 10(−4)), and lowest for CA (4.96 × 10(−5)). The average mutation rate per generation for this sample of loci is 8.87 × 10(−4) (SE 2.57 × 10(−4)). There is a strong effect of initial repeat number, particularly for AT repeats, with mutation rate increasing with the length of the microsatellite locus in the progenitor line. Controlling for motif and initial repeat number, chromosome 4 exhibited an elevated mutation rate relative to other chromosomes. A survey of dinucleotide repeats across the entire Arabidopsis genome indicates that AT repeats are most abundant, followed by CT, and CA. The great majority of mutations were gains or losses of a single repeat. Several lines exhibited multiple step changes from the progenitor sequence, although it is unclear whether these are multi-step mutations or multiple single step mutations. Generally, the data are consistent with the stepwise mutation model of microsatellite evolution.